2015
DOI: 10.3168/jds.2013-7097
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different model diets on milk composition and expression of genes related to fatty acid synthesis in the mammary gland of lactating dairy goats

Abstract: This study examined the effects of different roughage diets on milk composition and the expression of key genes associated with fatty acid (FA) synthesis in the mammary gland of lactating dairy goats. Eight multiparous lactating goats (body weight=43.6±2.5kg, 90±12 d in milk) fitted with external pudic artery and subcutaneous abdominal vein catheters were assigned to 2 treatments in a crossover design. The goats were fed different roughage diets with a similar concentrate-to-roughage ratio. The diets were (1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…53 In an underfed sheep model, a reduction in Scd transcripts was observed, while no modifications to Scd expression were seen in the adverse overfed model. 54 However, although feeding over 3 weeks was sufficient to increase the expression of Scd transcripts in the mammary gland of dairy goats fed a quality modified diet, 15 an unbalanced diet during the peri-pubertal period did not modify mammary lipid metabolism during early pregnancy in our model.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…53 In an underfed sheep model, a reduction in Scd transcripts was observed, while no modifications to Scd expression were seen in the adverse overfed model. 54 However, although feeding over 3 weeks was sufficient to increase the expression of Scd transcripts in the mammary gland of dairy goats fed a quality modified diet, 15 an unbalanced diet during the peri-pubertal period did not modify mammary lipid metabolism during early pregnancy in our model.…”
Section: Discussionmentioning
confidence: 67%
“…Maternal diet‐induced obesity during both pregnancy and lactation negatively affected mammary gland function . Moreover, results showed that maternal exposure to protein restriction could change fatty acid metabolism in the mammary gland and thus modify milk composition . For these reasons, the neonatal period is also considered as critical through the consumption of maternal milk, the composition of which may vary depending on the dam's diet and thus have long‐term effects on offspring health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular FAs were extracted according to a previously described procedure (Zhang et al ., 2015) with modifications (online Supplementary Materials and Methods).…”
Section: Methodsmentioning
confidence: 99%
“…Diets with different qualities of forages had distinct effects on milk FA composition, relating the expression of lipid metabolism‐related genes to the milk FA composition may be a key issue to milk FA regulating mechanisms (Chilliard, Ferlay, & Mansbridge, ; Mach et al., ). A diet with Chinese wildrye and alfalfa hay as the main forages was shown to increase the milk yield, the contents of milk fat and protein, and the expression of mammary lipogenic enzymes compared with corn stover as the forage fed to ruminants (Zhang, Ao, Khas‐Erdene, Song, & Zhang, ). A diet with alfalfa hay as the main forage increased the milk yield and the milk protein content compared to corn stover as the main forage diet fed to cows (Zhu et al., ).…”
Section: Introductionmentioning
confidence: 99%